Assessment of thrombin generation in horses using a calibrated automated thrombogram. (9th February 2022) - Leclere, Mathilde; Chevalier, Zoé; Dubuc, Valérie; Beauchamp, Guy; Bédard, Christian
Abstract: Background: The amount of thrombin generated reflects the endogenous thrombin potential (ETP), which depends on the balance of pro‐ and anticoagulant factors. The calibrated automated thrombogram (CAT) allows for the direct measurement of thrombin generation during the clotting process. Objectives: (1) To describe the results of the CAT assay in horses, (2) to establish intra‐assay and intra‐ and interindividual variation of thrombin generation in healthy horses, and (3) to compare in vitro low‐molecular‐weight heparin (LMWH) sensitivity between healthy and sick horses. The hypothesis for the last objective is that inhibition of thrombin generation in sick horses requires higher heparin concentrations. Methods: The plasma of 10 healthy mixed breed horses was used for the determination of normal thrombin generation parameters (lag time, time to peak, peak thrombin concentration, and ETP). Five of the healthy horses were compared with five horses with systemic inflammatory response syndrome (SIRS). In vitro heparin sensitivity was determined using LMWH. Results: The intra‐assay variation was small (<5%) for all parameters. Relatively large intra‐ and interindividual variation were observed in healthy horses. Four of the five sick horses with SIRS had a thrombogram compatible with a hypercoagulable state. The in vitro heparin sensitivity test suggested decreased sensitivity to LMWH in hypercoagulable states. Conclusions: The CAT assay could detect coagulopathy in horses. In vivo experiments are needed to confirm that it can be used to monitor responses to LMWH therapy.